Quinolone antibiotics enhance denitrifying anaerobic methane oxidation in Wetland sediments: Counterintuitive results. (15th July 2022) - Zhao, Yuewen; Jiang, Hongchen; Wang, Xiuyan; Liu, Changli; Yang, Yuqi
Abstract: Denitrifying anaerobic methane oxidation (DAMO) plays an important role in the element cycle of wetlands. In recent years, the content of antibiotics in wetlands has gradually increased due to human activities. However, the impact of antibiotics on the ecological function of DAMO remains unclear. Here we studied the influence of three high-content quinolone antibiotics (QNs) on DAMO in the sediments of the Baiyangdian Wetland. The results show that QNs can significantly promote the potential DAMO rates. Moreover, the enhancement of potential DAMO rates is positively correlated with the dosage of QNs. This promotion effect of QNs on nitrate-DAMO can be attributed to the hormesis phenomenon or their inhibition of substrate competitors. As antibacterial agents, QNs inhibit nitrite-DAMO conducted by bacteria, but greatly promote nitrate-DAMO conducted by archaea. These results suggest that the short-term effect of QNs on DAMO in wetlands is promotion rather than inhibition. Graphical abstract: Image 1 Highlights: The potential DAMO rates in Baiyangdian wetland were higher than most other habitats. Quinolone antibiotics enhanced potential DAMO rates. The enhancement of DAMO by QNs has a significant dose effect. The promotion of DAMO by QNs was attributed to the promotion of nitrate-DAMO. The promotion of DAMO by QNs may be a phenomenon of hormesis or obtained by inhibiting substrate competitors.